Pengaruh Permainan Engklek Nutriranger sebagai Media Edukasi Gizi Seimbang terhadap Pengetahuan dan Sikap Siswa SD Muhammadiyah 1 Kota Malang - Aurelia Faza Sepbrina; Aprinia Dian Nurhayati; Rizka Silvia; Hilma Tsurayya; Tika Dwi Tama; Zahra Anggita Pratiwi; Afinatul Jannah; Putra Ananda Dzaky (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2026)
The Nutriranger engklek game is a traditional game that integrates balanced nutrition material through in-game question cards. Balanced nutrition education for elementary school-aged children is important because this period is the phase of forming eating behavior that will affect future health. Game media was chosen because it can increase active participation and student interest in the learning process. The purpose of this study was to examine the effect of engklek games on knowledge and attitudes related to the concept of balanced nutrition of students at Muhammadiyah 1 Elementary School, Malang City. The research design used was a pre-experimental with one-group pretest posttest. A total of 188 students of Muhammadiyah 1 Elementary School, Malang City who met the inclusion criteria were involved as respondents. This study has been approved based on ethics from the ethics committee of Malang State University with No. 01.07.09/UN32.14.2.8/LT/2025. The questionnaire used as a research instrument has been tested for validity and reliability. The data were processed and analyzed using descriptive tests and Wilcoxon signed rank tests, showing that the average knowledge score after education was 72.8±16.0 and the average attitude score was 90.6±9.9. These data indicate an increase in knowledge of 7.9 points and an increase in attitude of 5.1 points. There is a significant effect (p<0.001) of using the Engklek game as a nutrition education medium in improving knowledge and attitudes. The Engklek Nutriranger game has the potential to be an innovative nutrition education medium based on traditional games to improve knowledge and attitudes about balanced nutrition in elementary school children.